(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
هدف البحث إلى التعرف على الآثار السياسية والاجتماعية لشبكات التواصل الاجتماعي على المستخدمين من الشباب الجامعي، وكيف أثرت هذه الشبكات على العلاقات الاجتماعية للشباب وعلى تكوين آرائهم السياسية. وتكونت عينة البحث من (157) طالبا وطالبة منهم (70) ذكورا و(87) إناثا تم اختيارهم بطريقة عشوائية منتظمة، واستخدمت الباحثة الاستبيان كأداة لجمع المعلومات وتضمن الاستبيان (44) سؤالاً تمت الإجابة عليهم من قبل أفراد العينة. وتوصل البحث إلى النتائج التالية : 1-إن الإناث أكثر استخداما لشبكات التواصل الاجتماعي من الذكور . 2-كثرة استخدام شبكات التواصل الاجتماعي يؤدي إلى التأثير على مجريات المتغيرات السياسية . 3-كثرة استخدام شبكات التواصل الاجتماعي يؤدي إلى زيادة مشاركة الشباب في القضايا الوطنية . This paper aims to identify the socio-political effects of Social Media Networks on University students and to uncover the ways in which they have affected the social relations of those students especially as to reshaping their political outlooks. The research sample consisted of (157) students of which there are (70) male students while the other (87) are female ones. Those students were selected both systematically and randomly. To achieve this, the research has implemented a questionnaire as a tool to collect data. The questionnaire included (44) questions which were answered by the population of the sample. The paper has come with following conclusions: 1-The females were found to use the social Media Networks the most. 2-The overuse of social Media Networks affected the ongoing political changes. 3-The overuse of Social Media Networks increased the participation of the youth in national affairs.